Risks Mitigation Practices for Multi-Sourcing Vendors in Green Software Development: Risks Mitigation Practices for Multi-Sourcing Vendors - Salam, Muhammad; Khan, Siffat Ullah (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Green and sustainable software development is the cry of the day and vendors are constantly striving to develop such software that have less hazardous impact on environment, economy and human beings. However developing green software in the context of software multi-sourcing is not a risk free activity. Software development multi-sourcing vendor organizations have focused on the adaptation of green practices in software development projects. In our previous study we have identified eight critical risk factors (CRFs) via systematic literature review (SLR) process, in the development of green and sustainable software. These CRFs are: ‘lack of green RE practices’, ‘high power consumption’, ‘high carbon emission throughout the software development’, ‘poor software design (architectural, logical, physical and user interface)’, ‘lack of ICTs for coordination and communication’, ‘high resources requirements’, ‘lack of coding standards’, and ‘lack of green software development knowledge’. The proactive management of the identified risks might allow software development multi-sourcing vendor organizations to develop green and sustainable software successfully. In this study we have presented the identified 76 practices for addressing the aforementioned eight critical risk factors. The practices were extracted from sample of (N=102) research papers via SLR process. We have validated the identified 76 solutions/practices from 108 relevant experts in software development multi-sourcing industry via questionnaire survey. The findings of this study may help vendor organizations to address/mitigate the CRFs using the identified solutions in order to develop green and sustainable software in multi-sourced software projects.